Wiskott-Aldrich syndrome iPS cells produce megakaryocytes with defects in cytoskeletal rearrangement and proplatelet formation - Ingrungruanglert, Praewphan; Amarinthnukrowh, Pramuk; Rungsiwiwut, Ruttachuk; Maneesri-le Grand, Supang; Sosothikul, Darintr; Suphapeetiporn, Kanya; Israsena, Nipan; Shotelersuk, Vorasuk (Thrombosis and Haemostasis, 2015)
Wiskott-Aldrich syndrome (WAS) is an X-linked recessive disorder characterised by microthrombocytopenia, complex immunodeficiency, autoimmunity, and haematologic malignancies. It is caused by mutations in the gene encoding WAS protein (WASP), a regulator of actin cytoskeleton and chromatin structure in various blood cell lineages. The molecular mechanisms underlying microthrombocytopenia caused by WASP mutations remain elusive. Murine models of WASP deficiency exhibited only mild thrombocytopenia with normal-sized platelets. Here we report on the successful generation of induced pluripotent stem cell (iPSC) lines from two patients with different mutations in WASP (c.1507T>A and c.55C>T). When differentiated into early CD34+ haematopoietic and megakaryocyte progenitors, the WAS-iPSC lines were indistinguishable from the wild-type iPSCs. However, all WAS-iPSC lines exhibited defects in platelet production in vitro. WAS-iPSCs produced platelets with more irregular shapes and smaller sizes. Immunofluorescence and electron micrograph showed defects in cytoskeletal rearrangement, F-actin distribution, and proplatelet formation. Proplatelet defects were more pronounced when using culture systems with stromal feeders comparing to feeder-free culture condition. Overexpression of WASP in the WAS-iPSCs using a lentiviral vector improved proplatelet structures and increased the platelet size. Our findings substantiate the use of iPSC technology to elucidate the disease mechanisms of WAS in thrombopoiesis.
Keywords: Wiskott-Aldrich syndrome; WASP; iPSCs; platelet; thrombopoiesis